2019
DOI: 10.1007/s12008-018-00527-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postural freedom to increase the neutral positions during laparoscopic surgery

Abstract: Laparoscopic technique has demonstrated numerous advantages compared to open conventional surgery. Nevertheless, this procedure increases the surgeons fatigue and thus, the potential to commit errors that may harm the patient during the operation. The post-surgery pain is also augmented because the surgeons are forced to adopt non-neutral postures during the practice. This study reveals how a Postural Freedom element could help surgeons to improve the postural hygiene. During this study, thirteen participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Different studies already indicated the forced non-neutral positions as the main cause of musculoskeletal problems for laparoscopic surgeons [3], [4]. In our experiment, the results showed the control instrument highest activity in muscles trapezius and deltoid (Fig.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Different studies already indicated the forced non-neutral positions as the main cause of musculoskeletal problems for laparoscopic surgeons [3], [4]. In our experiment, the results showed the control instrument highest activity in muscles trapezius and deltoid (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…However, for surgeons, these procedures have some complications. MIS procedures require more effort, concentration, cause more mental stress than open procedures, and force surgeons to adopt non-neutral postures with phalanges, hands, wrists and arms [3], [4]. Poor H. M. Pace-Bedetti and A. Conejero Rodilla are with the Instituto de Diseño y Fabricación (IDF), Universitat Politècnica de València (UPV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation